Genomic analysis of head and neck cancer cases from two high incidence regions (2018)
We investigated how somatic changes in HNSCC interact with environmental and host risk factors and whether they influence the risk of HNSCC occurrence and outcome. 180-paired samples diagnosed as HNSCC in two high incidence regions of Europe and South America underwent targeted sequencing (14 genes) and evaluation of copy number alterations (SCNAs). TP53, PIK3CA, NOTCH1, TP63 and CDKN2A were the most frequently mutated genes. Cases were characterized by a low copy number burden with recurrent focal amplification in 11q13.3 and deletion in 15q22. Cases with low SCNAs showed an improved overall survival. We found significant correlations with decreased overall survival between focal amplified regions 4p16, 10q22 and 22q11, and losses in 12p12, 15q14 and 15q22. The mutational landscape in our cases showed an association to both environmental exposures and clinical characteristics. We confirmed that somatic copy number alterations are an important predictor of HNSCC overall survival.